2015
DOI: 10.4236/jwarp.2015.710065
|View full text |Cite
|
Sign up to set email alerts
|

Turkey Creek—A Case Study of Ecohydrology and Integrated Watershed Management in the Low-Gradient Atlantic Coastal Plain, USA

Abstract: Water yield, water supply and quality, wildlife habitat, and ecosystem productivity and services are important societal concerns for natural resource management in the 21 st century. Watershedscale ecohydrologic studies can provide needed context for addressing complex spatial and temporal dynamics of these functions and services. This study was conducted on the 5240 ha Turkey Creek watershed (WS 78) draining a 3 rd order stream on the Santee Experimental Forest within the South Carolina Atlantic Coastal Plain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…There are also perennially wet locations adjacent to streams, and at least one significant spring mouth (Blue Spring, Echaw Creek, Berkeley County, SC, USA) was found during an investigation for potential GDE sites in the FMNF [28], in addition to at least one of the deeper partially-infilled solution depressions. While most of these features receive direct rainfall or shallow surface runoff from adjacent uplands, the presence of a shallow water table in this landscape, where the long-term average annual precipitation (1370 mm) is higher than the long-term annual potential [25,26].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…There are also perennially wet locations adjacent to streams, and at least one significant spring mouth (Blue Spring, Echaw Creek, Berkeley County, SC, USA) was found during an investigation for potential GDE sites in the FMNF [28], in addition to at least one of the deeper partially-infilled solution depressions. While most of these features receive direct rainfall or shallow surface runoff from adjacent uplands, the presence of a shallow water table in this landscape, where the long-term average annual precipitation (1370 mm) is higher than the long-term annual potential [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The sandy-loam texture of the soils and sediments is also an important factor. Some cases in point are studies of the water table response in three locations in the coastal plain region [26,39], and data have indicated that the specific yield of the surficial aquifer sediments was 0.1 or less, such that 5 mm of water loss by evapotranspiration (ET) can cause the water table depth to drop by at least 5 cm [40][41][42]. A comparable study in a drier climate, that used water table hydrograph data to understand groundwater recharge, found that the management of eucalypt stands in Australia can affect the water balance, but that the landscape position in that region was more important [32,33].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations